Everyday Salads - Edited by Kistner, Stephanie (Millers Point Murdoch Books, 2004)
Long dismissed as depressing health food, salads have stepped back into the limelight as a fabulous and versatile option. This book includes delicious variations from around the world, with simple, easy-to-follow instructions on how to create them.
Include Color Illustrations, Glossary and Index
Keywords: Salads -- Cooking